Exploring filamentous fungi depolymerization of corn stover in the context bioenergy queuing operations. (2nd December 2021) - Wendt, Lynn M.; Wahlen, Bradley D.; Walton, Michelle R.; Nguyen, Jason A.; Lin, Yingqian; Brown, Rebecca M.; Zhao, Haiyan
Abstract: Recalcitrance of lignocellulosic feedstocks to depolymerization is a significant barrier for bioenergy production approaches that require conversion of monomeric carbohydrates to renewable energy sources. This study assesses how low‐cost modifications in the supply chain can be transformed into targeted pretreatments in the context of the entire bioenergy supply chain. This research aims to overcome the physiochemical barriers in corn stover that necessitate increased severity in downstream conversion in terms of chemical loading, temperature, and residence time. Corn stover samples were inoculated with a selective ( Ceriporiopsis subvermispora ) and nonselective ( Phanerochaete chrysosporium ) lignin‐degrading filamentous fungal strains, then stored aerobically to determine the working envelope for fungal pretreatment to achieve lignin degradation. Dry matter loss and gross chemical makeup of corn stover varied by the length of treatment (2 and 4 weeks) and by the moisture content of the treated corn stover samples (40% and 60%, wet basis). Dry matter loss in P . chrysosporium inoculated biomass was elevated compared to C . subvermispora inoculated biomass; however, treatment also induced additional chemical composition changes suggestive of depolymerization. These results highlight that fungal treatment approaches must balance the loss of convertible material with the potential for reduction in recalcitrance. Techno‐economic assessment (TEA) of fungal pretreatment in a short‐term queuing system indicated the viability of this approach compared to conventional queuing operations. Total queuing system cost was estimated at 1.65/ton of biomass stored. After applying the credit of 1.48/ton from energy savings in the conversion phase using fungal pretreated biomass, the total system cost was 0.80 lower than traditional biomass queuing approach. While the TEA results suggested that treating biomass with C . subvermispora is the most economically viable storage method in the designed fungal‐assisted queuing system, future research should focus on additional fungal depolymerization such as those observed in the P . chrysosporium inoculated biomass. Abstract : Recalcitrance of lignocellulosic feedstocks to depolymerization is a significant barrier for bioenergy production approaches that require conversion of monomeric carbohydrates to renewable energy sources. This study assesses how low‐cost modifications in the supply chain can be transformed into targeted pretreatments in the context of the entire bioenergy supply chain. Techno‐economic assessment (TEA) of fungal pretreatment in a short‐term queuing system indicated the viability of this approach compared to conventional queuing operations.